Advances in discrete differential geometry - Bobenko, Alexander I (Springer Open, 2016)
A book on a newly emerging field of discrete differential geometry and an excellent way to access this exciting area. It surveys the fascinating connections between discrete models in differential geometry and complex analysis, integrable systems and applications in computer graphics.